2018
DOI: 10.2320/matertrans.md201721
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivity of Reducing Graphene Oxide and Titanium Dioxide Composite for Cinnamic Acid Degradation

Abstract: Reducing graphene dioxide (rGO) and titanium dioxide (TiO 2) composites with various rGO/TiO 2 ratios were prepared by hydrothermal method, in which rGO was synthesized from graphene powder according to modified Hummers method using microwave. Physico-chemical characteristics of the samples were investigated by the methods of N 2 adsorption-desorption measurements, X-ray diffraction, Raman, Fourier transform infrared spectroscopy (FT-IR), UV-Vis spectroscopy, scanning electron microscopy (SEM) and transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…These electrons oxidize organic pollutants 15,16) by producing free hydroxyl radicals (•OH) at higher concentration and faster by using UV light. 17) Photocatalyst materials have been used for environmental treatment 18,19) and, over recent decades, several inorganic semiconductors have been studied due to their high oxidative performance without requiring chemicals or high temperatures. 20) They have been used in photovoltaic and photodegradation of organic pollutants in air and water.…”
Section: Introductionmentioning
confidence: 99%
“…These electrons oxidize organic pollutants 15,16) by producing free hydroxyl radicals (•OH) at higher concentration and faster by using UV light. 17) Photocatalyst materials have been used for environmental treatment 18,19) and, over recent decades, several inorganic semiconductors have been studied due to their high oxidative performance without requiring chemicals or high temperatures. 20) They have been used in photovoltaic and photodegradation of organic pollutants in air and water.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the visible range of the spectrum, TiO 2 does not have photocatalytic activity due to its wide bandgap (3.2 eV in case of anatase) [5,6]. In order to activate photodegradation in the visible range, which would make this process cheaper by using solar light, TiO 2 can be combined with different materials to produce ternary compounds, doping [1,[6][7][8][9][10], nitriding [11], decorating [2] or composites fabrication [7]. The synergetic activity of the external element or compound and the TiO 2 matrix enhances visible light absorption and thus photocatalysis can be produced.…”
Section: Introductionmentioning
confidence: 99%
“…The sixth paper by Nguyen et al showed photoactivity of reducing graphene oxide and titanium dioxide composite for cinnamic acid degradation. 195) In summary, recent trends in nanostructured functional materials and their applications were introduced in this paper by the survey of the special issues related to the international symposia that we organized between 2013 and 2017, which are summarized on Table 1. This field covers a wide area of the materials science, then there are many papers not included in this paper.…”
mentioning
confidence: 99%